Working with clay - Peterson, Susan 1925-2009; Peterson, Jan (Laurence King Publishing, 2009)
"Working with clay is crafted not only to inspire and teach the beginning student of ceramics, but also to provide new ideas to advanced ceramists about clayworking through colorful photographs and clear descriptions of the processes involved. In an engagingly written text, the authors encourage creative exploration and appreciation of one of our oldest arts. The third edition is thoroughly updated throughout"--Provided by publisher.